Increasing task complexity and ice hockey skills of youth athletes - Fait, P. E.; McFadyen, B. J.; Reed, N.; Zabjek, R.; Taha, T.; Keightley, M. (Perceptual and Motor Skills, 2011)
The objective of this pilot study was to investigate the effects on cognitive performance of progressively adding tasks specific to ice hockey (skating, stick handling, and obstacle avoidance) during a visual interference task (Stroop Color Word Test-interference condition). In addition, the effects on locomotor performance of progressively adding tasks of stickhandling, visual interference, and obstacle avoidance related to maximal skating speed and minimal obstacle clearance were investigated in eight male athletes ages 10 to 12 years. Results revealed decreased performance on both cognitive and physical measures with increased task complexity, suggesting that adding complexity to an environment influences hockey skill performance.